Dampak kebijakan keringanan pajak terhadap penerimaan pajak, tax ratio, dan perubahan penerimaan pajak: Analisis pengampunan pajak, sunset policy, dan program pengungkapan sukarela di Indonesia - Kanna Ewanan, Frias Valentino; Sari, Diana (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Since 1964 until now, in 2022, the government of the Republic of Indonesia has had a habit of forgiving taxpayers who do not comply with tax regulations, such as by forgiving administrative sanctions or criminal sanctions. This study aims to determine the impact of tax relief policies on tax revenues, tax ratios, and changes in tax revenues. This study uses a qualitative approach by analyzing secondary data. The results of this study are that the application of tax relief policies (Tax Amnesty, Sunset Policy, or Voluntary Disclosure Program) in 1964, 1965, 1966, 1967, 1984, 2008, 2009, 2016, and 2022 is a door to pave the way for injustice in the Republic of Indonesia because, as long as the policy was running, only the Sunset Policy in 2008 was quite successful. Researchers also consider that this policy is one that violates the fifth precept of Pancasila because people who have obeyed will feel no longer valued. Then, this can also result in money laundering as long as the tax relief policy is implemented because the ransom money or its equivalent is not questionable.